Alpha oscillations and their impairment in affective and post-traumatic stress disorders. (September 2016) - Eidelman-Rothman, Moranne; Levy, Jonathan; Feldman, Ruth
Highlights: Alpha rhythm plays a pivotal role in cognitive, perceptual, and social processes. We review studies on alpha rhythm in depression, anxiety, OCD, and PTSD. Studies point to associations between aberrant alpha patterns and these disorders. We discuss methodological issues and future directions. Studying alpha's role in social contexts may provide new window to these disorders. Abstract: Affective and anxiety disorders are debilitating conditions characterized by impairments in cognitive and social functioning. Elucidating their neural underpinnings may assist in improving diagnosis and developing targeted interventions. Neural oscillations are fundamental for brain functioning. Specifically, oscillations in the alpha frequency range (alpha rhythms) are prevalent in the awake, conscious brain and play an important role in supporting perceptual, cognitive, and social processes. We review studies utilizing various alpha power measurements to assess abnormalities in brain functioning in affective and anxiety disorders as well as obsessive compulsive and post-traumatic stress disorders. Despite some inconsistencies, studies demonstrate associations between aberrant alpha patterns and these disorders both in response to specific cognitive and emotional tasks and during a resting state. We conclude by discussing methodological considerations and future directions, and underscore the need for much further research on the role of alpha functionality in social contexts. As social dysfunction accompanies most psychiatric conditions, research on alpha's involvement in social processes may provide a unique window into the neural mechanisms underlying these disorders.